Environmental dependence of the galaxy stellar mass function in the Dark Energy Survey Science Verification Data - Etherington, J.; Thomas, D.; Maraston, C.; Sevilla-Noarbe, I.; Bechtol, K.; Pforr, J.; Pellegrini, P.; Gschwend, J.; Carnero Rosell, A.; Maia, M. A. G.; Costa, L. N. da; Benoit-Levy, A.; et al. (Oxford Univ Press, 2017)
Measurements of the galaxy stellar mass function are crucial to understand the formation of galaxies in the Universe. In a hierarchical clustering paradigm, it is plausible that there is a connection between the properties of galaxies and their environments. Evidence for environmental trends has been established in the local Universe. The Dark Energy Survey (DES) provides large photometric data sets that enable further investigation of the assembly of mass. In this study, we use similar to 3.2 million galaxies from the (South Pole Telescope) SPTEast field in the DES science verification (SV) data set. From grizY photometry, we derive galaxy stellar masses and absolute magnitudes, and determine the errors on these properties using Monte Carlo simulations using the full photometric redshift probability distributions. We compute galaxy environments using a fixed conical aperture for a range of scales. We construct galaxy environment probability distribution functions and investigate the dependence of the environment errors on the aperture parameters. We compute the environment components of the galaxy stellar mass function for the redshift range 0.15 < z < 1.05. For z < 0.75, we find that the fraction of massive galaxies is larger in high-density environment than in lowdensity environments. We show that the low-density and high-density components converge with increasing redshift up to z similar to 1.0 where the shapes of the mass function components are indistinguishable. Our study shows how high-density structures build up around massive galaxies through cosmic time.
Keywords: galaxies: clusters: general; galaxies: evolution; galaxies: formation; galaxies: photometry; galaxies: statistics